Beyond intrapreneurship : The metamorphosis of large corporations - Norburn, David; Manning, Kingsley; Birley, Sue (Cranfield School of Management, 1985)
In the last two decades, companies have experimented upon the axes of centralisation and decentralisation, of formal and informal planning systems, and of 'tight' and 'loose' reins for effecting control. Concurrently academics have commentated upon these phenomena in an attempt to both conceptualise the process and to relate certain paradigms to corporate performance. Yet essentially, much of this commentary assumes models of organisation structures based upon a LINEAR approach to strategy formation which practising managers abandoned as a result of the trading turbulence of the mid-1970s. A mismatch therefore exists between theory and practice. Many companies, having heavily decentralised, are placing emphasis upon intra-company entrepreneurship (intrapreneurship) as a means of implementing ADAPTIVE strategies. However, we consider that intrapreneurship is but one option to larger corporations, and that a new approach to the strategy/structure relationship be considered ¬one which incorporates the third dimension of ownership and trades off corporate sovereignty and direct control within a federal context, for a spectrum of options, many external to existing ownership structures.Our model is essentially metamorphic implying cathartic change, not an incremental adaption more suited to LINEAR strategy. This paper therefore reviews the constraints of traditional strategy/structure relationships, proposes a model related to the anticipated trading conditions of the next decade, and recommends the removal of existing corporate legislation concerned with anti-trust and monopoly law.